Assessing the Quality of Teaching and Learning in Secondary Schools adopting British Council Standards in Light of Academic Achievement. - et. al., Istiklal Abbas Wishah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Assessing the quality of teaching and learning in secondary schools that adopted the standards of the British Council in the light of academic achievement is the key objective of this research. The researchers employed the descriptive analytical approach, and the research sample consisted of two middle schools, namely - Al-Hashmiyat Intermediate School for Girls and Al-Zubayr Intermediate School for Girls and Al-Ramah Al-Awali Preparatory School for Boys in Basra Governorate for the final classes. The researchers collected the results of the ministerial exams for the first and second attempts for all school students for three academic years, one year before applying the standards and two years after applying them. The researchers used the one-way analysis of variance to discover the differences between the arithmetic averages, and the L.S.D test to extract the dimensional comparisons between school years. The results showed that there were statistically significant differences between the students’ average scores in the general average according to the variable of the academic year 2016/2017 before the applying to the third intermediate class. The differences were not significant for the preparatory stage of the literary branch. In light of the results of the research, the researchers presented a number of recommendations and suggestions.